Personal protective equipment (PPE) related adverse skin reactions among healthcare workers at the main COVID-19 isolation center in Barbados - Bharatha, Ambadasu; Krishnamurthy, Kandamaran; Cohall, Damian; Rahman, Sayeeda; Forde, Corey A.; Corbin-Harte, Rhea; Ojeh, Nkemcho; Kabir, Russell; Parsa, Ali Davod; Rabbi, Ahbab Mohammad Fazle; Majumder, Md Anwarul Azim (Frontiers in Public Health, 2022)
Background: The use of personal protective equipment (PPE) reduces the risk of transmission of infectious agents significantly among healthcare workers (HCWs). The study aimed to investigate the prevalence and characteristics of PPE-related adverse skin reactions among HCWs working at the main COVID-19 isolation centre in Barbados. Methods: A cross-sectional web-based online survey was conducted during April June 2021 which recorded demographic information, details of PPE use and adverse skin reactions including severity and duration of onset of symptoms. Results: Most of the respondents used PPE for consecutive days (77.9%), 1-6 hours/day (59.2%), and more than a year (62.5%). Fewer than half of the participants (45.6%) experienced adverse skin reactions from the use of PPE. The reactions were mostly observed in the cheeks (40.4%) and nose bridges (35.6%). Females had more reactions than their male counterparts (p=0.003). The use of N95 masks and a combination of surgical and N95 masks produced adverse effects predominantly in the ears (60%) and cheeks (56.4%). Binary logistic regression showed that female HCWs (OR = 5.720 95% CI: 1.631, 20.063), doctors (OR = 5.215 95% CI: 0.877, 31.002), and longer duration of PPE use (>1 year) (OR = 2.902 95% CI: 0.958, 8.787) caused a significantly higher prevalence of adverse skin reactions. Conclusion: The PPE-related skin reactions were common among HCWs which mainly occurred due to prolonged use. Preventive measures inclusive of appropriate training of HCWs on the use of PPE are recommended to minimize these adverse events.